An Electronic Synapse Based on 2D Ferroelectric CuInP2S6. (9th November 2020) - Li, Bochang; Li, Sifan; Wang, Han; Chen, Li; Liu, Liang; Feng, Xuewei; Li, Yesheng; Chen, Jingsheng; Gong, X.; Ang, Kah‐Wee
Abstract: Memristors with biological synaptic behaviors and functions have been intensively studied as an important component for neuromorphic computing system, which hold promise to address the power consumption issue in modern computers based on von Neumann architecture. However, the resistive switching mechanism that relies on the stochastic formation of conductive filaments leads to poor cycle‐to‐cycle (temporal) and cell‐to‐cell (spatial) variations for filamentary memristors. The emergence of memristors based on 2D ferroelectric materials can potentially avoid these issues. Here, a vertical Au/CuInP2 S6 (CIPS)/Ti diode is demonstrated using exfoliated ferroelectric CIPS flake. Through ferroelectric switching, the CIPS diode realizes resistive switching with a ratio larger than 6 × 10 3 . The endurance measurement shows a small set and reset voltage variation of 5.3% and 9.1%, respectively. Key synaptic behaviors including spike‐time‐dependent plasticity, paired‐pulse‐facilitation, and paired‐pulse‐depression are successfully mimicked, manifesting the potential application of CIPS diode in a neuromorphic computing system. Moreover, pattern learning and memory behaviors are emulated using a 3 × 3 CIPS crossbar array. Abstract : A ferroelectric diode is fabricated using exfoliated CuInP2 S6 (CIPS) flake. Ferroelectric switching leads to resistive switching (RS) in a CIPS diode, and a series of synaptic features are mimicked based on this RS behavior. In addition, pattern learning and memorization behaviors are emulated by a 3 × 3 CIPS crossbar array.